Readings of a Dictator (KULT_online, 2011)
Timothy W. Ryback received his PhD from Harvard University (US) and has been a columnist for The New Yorker, The New York Times and the International Herald Tribune. His most recent book describes Hitler’s peculiar approach towards reading whilst offering a panoramic view of the dictator’s own book collection. Ryback here focuses his attention in particular on ten books, which Hitler either bought himself or received as gifts (from, for example, Leni Riefenstahl and Dietrich Eckart). For each of these books the author reconstructs the circumstances in which Hitler came into possession of it as well as its influences on his thought. Overall a very intriguing book in which Hitler's biography, history and personal anecdotes are merged, offering readers a non-conventional depiction of the dictator.